Music engagement as a resource for health and well-being: an investigation of psychological and psychobiological correlates in clinical and non-clinical samples - Köhler, Friederike (2022)
To maintain and improve health and well-being, human beings have naturally turned to music for thousands of years. Nowadays, music is an essential part of everyday life, though the engagement with music can occur in a multitude of ways and contexts. Correspondingly, researchers have become increasingly interested in exploring the health and well-being benefits of music engagement in the domains of music therapy and music medicine, music education, community music, and everyday uses of music. Since the findings from these different domains are rarely integrated, the aim of the present thesis was to investigate the impact of music engagement on psychological and psychobiological aspects of health and well-being in clinical settings (music therapy) and non-clinical settings (everyday music engagement) and to discuss their potential similarities and differences. Therefore, a daily diary study, a meta-analysis, and a randomized controlled trial in different settings of music engagement were conducted. In a non-clinical setting, the daily diary study with hobby musicians (Manuscript 1) showed that autonomous motivation to engage in music making predicted higher affective well-being and life satisfaction. Further, results suggested flow experiences as a mediating mechanism. Regarding a clinical setting, the aim of the systematic review and meta-analysis in Manuscript 2 was to gain a comprehensive overview of the impact of music therapy in oncology on health and well-being. Findings revealed beneficial effects on psychological well-being, quality of life, and physical symptom distress, while the frequency and type of music therapy moderated the effect on psychological well-being. To gain more thorough insights into the palliative care setting, a randomized controlled trial was conducted to evaluate a newly developed biographical music therapy showing beneficial effects on psychospiritual outcomes and treatment satisfaction compared to a relaxation intervention (Manuscript 3). Though there were no treatment effects on psychobiological outcomes, both the experimental and control group showed a significant reduction of cortisol and mean heart rate over time (Manuscript 4). As one of the few works combining research and theories of music psychology and music therapy, the discussion of these exemplary findings outlined similarities of music engagement in clinical and non-clinical settings in terms of health and well-being related study outcomes as well as possible underlying mechanisms such as flow experiences and psychobiological stress reduction. Further, findings also indicated differences in terms of the motivation to engage with music, the type of music engagement, and the presence of a therapeutic relationship. Nonetheless, a joint agenda of these disciplines may have highly relevant implications for both research and practice in prevention and health care with regard to improving the quality of studies and consolidating the role of music engagement as a resource for health and well-being in communities and public systems.